Antimicrobial Peptides, Their Production, and Potential in the Fight Against Antibiotic-Resistant Pathogens - Margarita Saubenova; Alexander Rapoport; Zhanerke Yermekbay; Yelena Oleinikova (Fermentation)
The article reviews the literature on antimicrobial peptides (AMPs) that exhibit unique antimicrobial mechanisms, such as broad-spectrum activity, low development of antimicrobial resistance, and the ability to modulate the immune response of the host organism. Information is provided on the significant potential of AMPs in the fight against pathogens threatening human health and food safety. Enrichment of the human diet with biologically active peptides obtained using the proteolytic activity of lactic acid bacteria (LAB) is proposed as a simple, accessible, and viable alternative to antibiotics that does not have a harmful side effect. The review briefly covers the methods for obtaining AMPs and features of the LAB proteolytic system responsible for producing bioactive peptides in the environment. It has been shown that using various LAB strains makes it possible to produce high-quality whey-based beverages with different directions of antagonistic activity against opportunistic pathogens and helps optimize the gastrointestinal microbiota. It is assumed that such drinks can reduce the dose of antimicrobials in the combined therapy of various infectious diseases and be a preventive measure against contagion and the spread of antimicrobial resistance.